2020
DOI: 10.5430/ijfr.v11n6p301
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Board and Firm Risk: An Emerging Market Perspective

Abstract: This study examines the relationship between board features and firm risk of listed companies in Colombo Stock Exchange for the period of 2010 to 2017. This research was carried out based on positivistic paradigm with the quantitative methodology. Secondary data were collected and analyzed using panel data analyze techniques to obtain quantitative measures of descriptive statistics, correlations, and regression analyses. The results show that the board features variables such as Board size, Women on board, Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…The results of this study are in line with research conducted by [64]; [4]; [65]; [74]; [62] Gender diversity has a negative effect on firm risk. This study is not in line with research [51] which states that gender diversity has a significant positive effect on firm risk and research [28]; [75] which shows there is no effect of gender diversity to firm risk.…”
Section: The Effect Of Gender Diversity On Firm Risksupporting
confidence: 89%
See 2 more Smart Citations
“…The results of this study are in line with research conducted by [64]; [4]; [65]; [74]; [62] Gender diversity has a negative effect on firm risk. This study is not in line with research [51] which states that gender diversity has a significant positive effect on firm risk and research [28]; [75] which shows there is no effect of gender diversity to firm risk.…”
Section: The Effect Of Gender Diversity On Firm Risksupporting
confidence: 89%
“…Previous research [62] stated that gender diversity had a significant positive effect on firm risk, research [4][4] showed the effect of gender diversity had a negative effect on firm risk and research results [3] stated the existence of female members have no effect on firm value. [63] describes the relationship between board diversity and firm value in the context of agency theory and based on board relationships as a means of control and monitor for the company.…”
Section: 8the Effect Of Gender Diversity On Firm Riskmentioning
confidence: 99%
See 1 more Smart Citation